Future creative text online - Charef, Abdelkader (Cybrarians Journal, 2015)
About the literary text - in our time - to achieve its Arab identity and privacy of civilization, and its ability to influence the other, through independence cognitive its own properties on the one hand the Arab perspective of life and openness to the world in accordance with the technical and creative foundations to ensure his safety that openness that does not lose its specificity, and whatever not, the renovation of the literary text is Absorb the currents of the times and keep up with the transformations while preserving the cultural Arab identity, spirituality and intellectual of the nation, taking into account the cultural specificities as the creativity of the Arab people, the new text is that out of the traditional paper-phase to the new e-phase represents a new creative experience topple the grounds on which it is based power authority of the ancient text, it employs mechanisms intensification of the movement of modern life that require entering the electronic age, who was wide open field for the marketing of "globalization", including in respect of knowledge, values ​​and composition trends and consumer tastes.